Foreign exchange reserves dynamics: Trade balance and external debt in an ecm analysis - Lili Ramahdani; Annisa Zavira (Jurnal Mantik, 2026)
This study examines the dynamics of foreign exchange reserves within an open economy framework by focusing on the roles of trade balance and external debt. In recent years, the stability of foreign exchange reserves has become a critical issue due to increasing external volatility, global economic uncertainty, and growing dependence on international trade and financial flows. This study aims to analyze both short-run and long-run relationships between trade balance, external debt, and foreign exchange reserves. The research employs an Error Correction Model (ECM) using quarterly data from 2016 to 2025. The results indicate that the trade balance has no significant effect in the short run but exhibits a positive and significant effect in the long  run on foreign exchange reserves. In contrast, external debt has a positive and significant impact in both the short run and long run. These findings suggest that foreign exchange reserves are influenced by a dynamic adjustment mechanism, where the real sector plays a dominant role in the long run, while the financial sector contributes more rapidly in the short run. The main contribution of this study lies in highlighting the asymmetric relationship between external sector variables and foreign exchange reserves, emphasizing the importance of adjustment processes toward long-run equilibrium. These findings are important for policy formulation aimed at maintaining foreign reserve stability through export strengthening, value-added improvement, and sustainable external debt management